Encountering early America - Winchcombe, Rachel (Book collections on Project MUSE., 2021)
Encountering early America traces the many cultural influences that shaped English understandings of the Americas in the sixteenth century. The book demonstrates that the first century of English engagement with America was dynamic, adaptive and had a lasting influence on exploration and settlement in the New World.